STRATEGIES TO STRENGTHEN FOOD SECURITY AMID THE COVID-19 PANDEMIC THROUGH TRAINING BUDIKDAMBER AND AQUAPONICS IN KEDUNG SOKA VILLAGE, PULO AMPEL SUBDISTRICT, SERANG REGENCY - Erlangga, Erlangga; Yudistira, Andrian; Maulana, Asroful; Maulida, Aulia; Sabrawijaya, Sabrawijaya (Nindikayla Institute, 2024)
COVID-19, which was declared a pandemic globally by WHO, is one of the family of viruses that attack humans, namely attacking the human respiratory tract. In March, Indonesia was horrified by COVID-19. Therefore, the Indonesian government imposed rules for the community to implement Work From Home (WFH) which is part of the Enactment of Restrictions on Community Activities (PPKM) to reduce the increasing growth rate COVID-19 cases. The impact of this policy is that it can cause a food crisis. One of the efforts that can be done to prevent the occurrence of food crisis is budikdamber (fishcultivation in ember) and aquaponics with the discovery of agricultural and fishery techniques that are as healthy as budikdamber and aquaponics are expected to help face the current problems. This activity has many benefits, including the fulfillment of household needs and improving the family economy. People who succeed with bukdidamber techniques can create business opportunities and increase the development amid the COVID-19 pandemic as it is now. After conducting Budikdamber (FishCultivation in Ember) and Aquaponics activities in Kedung Soka Village, Pulo Ampel Subdistrict, Serang Regency, which was carried out by KKM Bina Bangsa Group 35 Participants in Kedung Soka Village, the Kedung Soka community was very enthusiastic to participate in the training of Making Catfish Cultivation in Ember. Through the training, the community got new skills. related to overcoming the economic crisis caused by the Covid-19 Pandemic